Sudden Odynophagia and Globus—A Unique Presentation of a Nonsecreting Parathyroid Adenoma: A Case Report and Literature Review - Srikantha, Luxman; Amjad, Esmael H.; Beydoun, Rafic (Case Reports in Otolaryngology, 2020)
Parathyroid adenomas are most commonly diagnosed when symptoms consistent with primary hyperparathyroidism arise. However, certain parathyroid glands may enlarge without such symptoms. Described here is a case in which a patient presented with acute signs of unilateral cervical point tenderness, dysphagia, and odynophagia. Calcium and parathyroid hormone levels tested within normal range. Imaging revealed an enlarged right-sided mass, with compression of the trachea-esophageal groove and potentially the right recurrent laryngeal nerve. Surgical excision was performed, and final pathology revealed an infarcted parathyroid adenoma. Clinical symptoms promptly resolved thereafter. Current NIH criteria for parathyroidectomy include various symptoms of hyperparathyroidism but do not include the above findings. Nonsecreting parathyroid adenomas rarely cause laryngeal symptoms, as this has only been documented once before.